The Effect of Project-Based Blended Learning Model on Students’ Creative Thinking Skills in Global Warming Topic - Wayan Suana; Suzanna Wati; I Wayan Distrik; Margaretha Karolina Sagala; Daniel Rinaldi (Jurnal Ilmiah Pendidikan Fisika, 2023)
This paper investigates the effect of project-based blended learning (PBBL) on students' creative thinking skills, particularly in the context of global warming. The research employed a quasi-experimental design using a nonequivalent control group. The study involved 60 students from the 11th grade at SMAN 16 Bandar Lampung. The experiment group with 30 students studied global warming through the PBBL strategy, while the control group used full face-to-face project-based learning (PjBL). The instrument consists of six essay questions. Validity and reliability tests were conducted on the hypothesis test results, indicating significance at a level of less than 5 percent. Using the t-test, a significant difference was observed in the average creative thinking skills between the experiment and control groups. Moreover, the effect size score was 0.785 (high category), confirming the high impact of learning through PBBL. The average n-gain for creative thinking abilities was 0.793 (high) for the experimental class and 0.3791 (moderate) for the control class. It can be inferred that the PBBL model has a positive impact on enhancing students' creative thinking abilities. The research implies that PBBL has the potential to revolutionize traditional teaching methods, fostering students' creative thinking skills, especially when applied to complex global issues like climate change.